Pandemic and mental health: predictors of fear of coronavirus (covid-19) in Peruvian youth and adults - Soto Bustamante, Rocio (2024)
The COVID-19 pandemic impacted the mental health of thousands of young people and adults, especially in its initial phase, since the disease was perceived as an uncertain and continuous threat, resulting in the fear of the coronavirus becoming dysfunctional, generating psychological discomfort. The principal aim of the study was to evaluate the psychosocial variables that predict fear of the coronavirus and its dimensions, in a sample of 384 Peruvian youth and adults, women (64.5%) and men (35.5%), between the ages of 18 and 67 (M= 26.36, SD=9.17). The predictor variables evaluated were Uncertainty, Stress, and the Use of the media, using for their measurement the IUS-12, the PSS-10 and the Scales of Use of the media and Fear of the coronavirus that belong to the Questionnaire of the Psychological Impact of the Coronavirus by Sandín et al. (2020). The results of the multiple linear regression analyzes revealed a prediction model of fear of the global coronavirus with a large effect size (R2 = .28, p < .001) and of medium magnitude in the models to predict its dimensions, thus evidencing the predictive capacity of intolerance towards uncertainty, stress, and frequent use of the media. Likewise, sex, educational level and employment were significant variables in the models, and it seems the women and those people who have a low educational level or do not have a job experience a greater fear of COVID-19.